(untitled) (European Journal of Education, 2021)
This paper is focused on exploring the learning experiences of students of Faculty of Education Sciences, University of Elbasan, Albania, during the period of sudden movement from teaching in auditorium to the online learning environment due to the COVID-19 pandemic. The purpose of the study was to identify the positive and negative aspects of online learning as experienced by students, as well as to find out their preference for the most appropriate form of higher education delivery (face-to-face, hybrid, online) for young people of digital age. The methodology used in this study included an item-based questionnaire to collect data which was developed through a web-based application known as Google Forms and was delivered to students via Internet. Qualitative and quantitative analysis was undertaken for the answers obtained by the open-ended and closed-ended questions. The results of the study showed that the biggest challenge for all students was the immediate adaptation to the form of distance learning. Most of them had perceived the online learning dominated more by negative experiences than positive ones. The study concluded that new reality created by COVID-19 tested the current capacity of Higher Education Institutions regarding the ICT integration process in teaching. As this process was progressing very slowly, universities were found unprepared to transfer the teaching process from the auditorium to the online environment with the same quality. In order to meet the demands of the future, it is imperative that every university to plan strategically the increase investment towards its digital transformation.